Comparing the intraoperative and postoperative complications of the scalpel and electrocautery techniques for severing the inner layers of the lumbar disc during discectomy surgery - Hajilo, Parisa; Imani, Behzad; Zandi, Shirdel; Mehrafshan, Ali (Frontiers in Surgery, 2023)
Background: Due to the sensitivity of the surgical site and a higher probability of injury, the use of a scalpel and electrocautery to create an incision in the spine is discussed. In this study, we will compare the intraoperative and postoperative complications of the scalpel and electrocautery techniques for severing the inner layers of the lumbar disc during discectomy surgery .This study was conducted in Iran as a randomized controlled trial with double-blinding (1401). Sixty candidates for spine surgery were randomly divided into two groups of 30 using electrocautery (A) and a scalpel (B) based on available sampling. The VAS scale was used to assess postoperative pain. The duration of the incision and intraoperative blood loss were recorded. The infection and fluid secretions were determined using the Southampton scoring scale.Utilizing the Manchester scar scale, the wound healing status was evaluated. The SPSS version 16 software was used for data analysis (t-test, Mann-Whitney U, ANOVA).The electrocautery group had substantially lower bleeding, pain, and wound healing rates than the scalpel group (P>0.05). However, the electrocautery group had significantly longer surgical times, more secretions, and a higher infection rate than the scalpel group (P>0.05). In terms of demographic and clinical characteristics, there was no significant difference between the two groups (P<0.05).Electrocautery reduces postoperative hemorrhage and, potentially, postoperative pain in patients. However, as the duration of surgery increases, so does the duration of anesthesia, and patient safety decreases. Additionally, the risk of infection increases in the electrocautery group compared to the scalpel group, and the rate of wound healing decreases.